Molecular Cardiac Changes in Feline Hyperthyroidism and Hypertrophic Cardiomyopathy: Focus on Desmin, Calreticulin, and Interleukin-10 Expression - Izabela Janus-Ziółkowska; Joanna Bubak; Massimiliano Tursi; Cristina Vercelli; Rafał Ciaputa; Małgorzata Kandefer-Gola; Agnieszka Noszczyk-Nowak (Animals)
Feline hyperthyroidism is the most frequent endocrinopathy in adult and senior cats, frequently leading to cardiac changes characterised by a hypertrophic cardiomyopathy (HCM) phenotype, which may partially reverse with appropriate treatment. However, the structural and molecular alterations in the myocardium can persist and closely resemble those observed in hypertrophic cardiomyopathy. Despite this clinical overlap, protein expression patterns in the hearts of hyperthyroid cats remain poorly understood. This study aimed to evaluate the myocardial expression of desmin, a key contractile protein, as well as calreticulin and interleukin-10 proteins involved in cardiac remodelling and response to injury. Left ventricular samples were obtained from 16 hyperthyroid cats, 12 cats with HCM, and 10 healthy controls. Immunohistochemical staining was performed to assess the expression patterns of the selected proteins. Our findings revealed that, despite median left ventricular dimensions not being significantly different from ones observed in healthy animals, cats with hyperthyroidism exhibited similar alterations in desmin and interleukin-10 expression to those seen in HCM-affected cats. These changes were associated with cardiomyocyte degeneration and coronary artery narrowing, suggesting a shared pathway of myocardial injury independent of the primary disease.